ADDITIONAL FEEDING. FROM REGULATIONS TO INDIVIDUAL APPROACH - T.N. Sorvacheva; E.A. Gordeeva; E.N. Anikieva ("Paediatrician" Publishers LLC, 2011)
This article contains modern tendencies of additional feeding organization and its changes in history. These changes can be explained by a new conception of the meaning of additional feeding to a growing organism and about it's level of adaptation, that was shown on the example of industrially manufactured additional feeding products. Key words: additional feeding, children, baby food. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 45-48.)